2020
DOI: 10.1158/1940-6207.capr-20-0269
|View full text |Cite
|
Sign up to set email alerts
|

Upper Endoscopic Surveillance in Lynch Syndrome Detects Gastric and Duodenal Adenocarcinomas

Abstract: Lynch syndrome is a prevalent hereditary cancer predisposition syndrome. While colorectal cancer is the most common gastrointestinal (GI) cancer in Lynch syndrome, there is also increased risk of gastric and small intestinal cancers. Recommendations for upper GI cancer surveillance in Lynch syndrome vary widely with limited data supporting effectiveness. Herein, we collected data on individuals with a diagnosis of Lynch syndrome seen at our tertiary care referral center. We identified individuals who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 32 publications
0
37
1
Order By: Relevance
“…Another small, retrospective, single-institution study of 66 LS carriers (21 of whom underwent EGD surveillance) found that 19% of the screened individuals had potential precursor findings on UGE ( H. pylori , intestinal metaplasia) [ 24 ]. Our results are contrary to a more recent single-institution cohort of 217 LS carriers whom underwent UGE surveillance, where the prevalence of gastric intestinal metaplasia was low (8.3%) [ 26 ]. The prevalence of H. pylori infection was 28% in our cohort, which is consistent with the usual prevalence in Europe (around 30%) [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Another small, retrospective, single-institution study of 66 LS carriers (21 of whom underwent EGD surveillance) found that 19% of the screened individuals had potential precursor findings on UGE ( H. pylori , intestinal metaplasia) [ 24 ]. Our results are contrary to a more recent single-institution cohort of 217 LS carriers whom underwent UGE surveillance, where the prevalence of gastric intestinal metaplasia was low (8.3%) [ 26 ]. The prevalence of H. pylori infection was 28% in our cohort, which is consistent with the usual prevalence in Europe (around 30%) [ 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, there is no consensus about the appropriate screening for upper gastrointestinal cancer in Lynch syndrome ( Table 1 ). Guidelines are all based on imprecise or small-sized epidemiological studies, due to the lack of UGE surveillance studies [ 24 , 25 , 26 ]. Nevertheless, Capelle et al have reported that, in a large Dutch cohort of individuals with Lynch syndrome, gastric cancer cases were mostly diagnosed after 45 years and that a family history of gastric cancer was a poor prognosticator of an increase in individual risk [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveillance intervals also remain controversial. Recent data supports short surveillance intervals, with the majority of LS-related UGI cancers being detected within 2 years of a prior surveillance upper endoscopy [ 9 , 11 ]. In the setting of a shorter surveillance interval, we believe that UGI surveillance procedures should always be performed concurrently with a lower GI surveillance procedure, to minimize procedural burden.…”
mentioning
confidence: 97%
“…We recently described our outcomes from UGI surveillance in LS. [ 9 ] Among 295 with LS, 217 (73.6%) underwent at least 1 upper endoscopy, with 11 (3.7%) patients being diagnosed with an UGI cancer: one esophageal squamous cell carcinoma, six gastric adenocarcinomas, and four duodenal adenocarcinomas. Among the 11 persons who developed an UGI cancer, 5 of these cancers were detected during surveillance, while the remainder were discovered during work-up of symptoms.…”
mentioning
confidence: 99%